Characteristics of Tropical Low Land Rain Forests of South Western Arunachal Pradesh - Banerjee, A. K. (Indian Forester, 1977)
Tropical rain forests of Indian sub-continent have not been studied in detail so far. Characteristica of the population, pattern of distribution of selected species, change in number of stems, diameter distributions, crop, heights etc. with 100 metres change in elevation have been studied in the forests of south western part of Arunachal Pradesh. The pattern ot distribution of selected species bave been worked out. It bas been concluded from the study of the data that apparently homogeneous rain forests are, in fact, haterolenous. The heterogeneity is mainly in frequency and abundance of varioul species. The pattern of distribution of individual species are clumped, random or uniform. It is tentatively suggested that in low level rain forests, the first critical level of change is reached at an elevation ot 600 to 700 metres.